Team-based learning vs. lecture-based learning in nursing: A systematic review of randomized controlled trials - Zhang, Qin; Tang, Xiumei; Zhao, Yanjie; Wang, Zhoufeng (Frontiers in Public Health, 2023)
In order to identify, appraise, and summarize randomized controlled trials (RCT) on the effectiveness of team-based learning (TBL) versus lecture-based learning (LBL) in nursing students. We searched PubMed, Ovid, Embase, Cochrane, CBM, VIP, CNKI, and WanFang databases from inception to 22th July 2022 to enroll RCTs that compared TBL versus LBL. The studies reporting the performance of nursing students receiving TBL pedagogy compared to those receiving traditional lecture-based learning (LBL) were enrolled to be analyzed. Scores of academic or nursing abilities were considered as the primary outcome, and the results of nursing competencies, students’ engagement with, behaviors, attitudes towards, experience, satisfaction or perceptions of TBL were considered as the secondary outcome. This systematic review was conducted following the guidelines of the Cochrane Reviewer’s Handbook and the Preferred Reporting Items for Systematic Reviews and Meta Analyses statement. A total number of 1009 of participants in 10 RCTs were enrolled in this study. Of the 10 RCTs, 8 studies investigated undergraduate students, one for vocational college students, and another one for secondary school students. The most commonly reported outcomes were class engagement survey towards TBL (n=8); students’ ability (n=5), academic knowledge or performance (n=4); students’ experience (n=4), satisfaction or perceptions of TBL (n=4). In general, this review suggested that the TBL was an effective pedagogy in improving academic performance, general ability in nursing students. However, most of the RCTs were low quality and high in risks of bias. High-quality trials are in need, and standard outcomes should be applied.